Association Between Serum Ceruloplasmin And Lipid Peroxidation Markers in Patients with Rheumatoid Arthritis - Khansaa Hatim Abdulijabar (International Journal of Medical Science and Dental Health, 2026)
Background: Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease with chronic synovial inflammation, immune system overstimulation and oxidative stress. Objective: To evaluate the serum levels of ceruloplasmin and some lipid peroxidation parameters (MDA, 4-HNE and 8-isoprostab) and to assess their correlation with severity of disease and between them in patients with rheumatoid arthritis (RA). Methods: This study is a case–control cross-sectional study that included 60 patients who have clinically diagnosed RA and 60 apparently healthy controls recruited from Al—Hilla Teaching Hospital. Patients were classified as having mild, moderate, and severe disease activity groups based on clinical severity assessment. Assessment of serum ceruloplasmin was carried out by enzyme linked immunosorbent assay (ELISA). As described in the Serum MDA, 4-HNE and 8-isoprostane levels were measured with quantitative biochemical immunoassay methodologies. Results: Compared with the health controls, the serum ceruloplasmin, MDA, 4-HNE, and 8-isoprostane levels were significantly higher in RA patients (P < 0.01). All studied biomarkers showed a stepwise increase in their concentrations from mild to moderate to severe RA; the highest concentrations were detected in the severe RA group. Ceruloplasmin had was a moderate positive and statistically significant correlation between ceruloplasmin and 8-isoprostane (r = 0.368, P = 0.002). Conclusion: Serum ceruloplasmin and lipoperoxidation biomarkers were significantly increased in RA patients and correlated directly with disease severity. The presence of a significant relationship between ceruloplasmin and the concentration of 8-isoprostane can suggest a nexus between the antioxidant response and lipid peroxidation in the pathophysiology of RA.